Demographic gaps or preparation gaps?: The large impact of incoming preparation on performance of students in introductory physics - Shima Salehi; Eric Burkholder; G. Peter Lepage; Steven Pollock; Carl Wieman (Physical Review Physics Education Research, 2019)
We have studied the impact of incoming preparation and demographic variables on student performance on the final exam in the standard introductory calculus-based mechanics course at three different institutions. Multivariable regression analysis was used to examine the extent to which exam scores can be predicted by a variety of variables that are available to most faculty and departments. The results are surprisingly consistent across the institutions, with only math SAT or ACT scores and concept inventory prescores having predictive power. They explain 20%–30% of the variation in student exam performance in all three cases. In all cases, although there appear to be gaps in exam performance if one considers only demographic variables (gender, underrepresented minority, first generation), once these two proxies of incoming preparation are controlled for, there is no longer a demographic gap. There is only a preparation gap that applies equally across the entire student population. This work shows that to properly understand differences in student performance, it is important to do statistical analyses that take multiple variables into account, covering both subject-specific and general preparation. Course designs and teaching better matched to the incoming student preparation will likely eliminate performance gaps across demographic groups, while also improving the success of all students.